INTEGRASI MATEMATIKA DAN NILAI KEISLAMAN DALAM PEMBELAJARAN MATEMATIKA UNTUK MEMBENTUK SISWA YANG BERKARAKTER ISLAMI DI SDN 100315 SANGGAPAPATI - Siregar, Haddad Alwi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
Mathematics is one of the compulsory subjects in elementary school. Therefore, it is expected that by introducing Islamic values in mathematics learning, students can learn mathematics and understand the greatness of Allah SWT. This research is motivated by the lack of students' understanding of Islamic values instilled in mathematics learning because mathematics material lacks a connection with Islamic values. This research was conducted at SDN 100315 Sanggapati, East Angkola Subdistrict, South Tapanuli and all students are predominantly Muslim. This research is a qualitative research that uses data collection methods through observation at elementary schools, interviews with SDN 100315 Sanggapati teachers, and learning documentation according to the lesson plan. The purpose of the research is to find out the integration of Islamic values and mathematics education in developing students with Islamic character at SDN 100315 Sanggapati.